Sunscreen Increasingly Overshadows Alternative Sun-Protection Strategies - Koch, S.; Pettigrew, S.; Strickland, M.; Slevin, Terry; Minto, C. (2016)
The present study assessed perceptions of effective sun-protection strategies among the general public and whether these perceptions have changed in recent years. During five summers from 2007/2008 to 2011/2012, 4217 adolescents and adults living in a region with very high levels of solar UV radiation participated in annual, cross-sectional telephone surveys. Respondents’ perceptions of the most effective sun-protection strategy were measured with a single open-ended question. In all survey years, sunscreen was the by far most frequently nominated sun-protection strategy, with an average mention rate of 71.0 %. The tendency to nominate sunscreen increased significantly over the 5-year study period and on average, was more common among adolescents compared to adults (81.6 vs 60.0 %) and females compared to males (73.6 vs 68.3 %). Despite respondents’ increasing tendency to nominate sunscreen as the most effective sun-protection strategy, health experts have voiced concerns about flawed application practices. Current sun-protection hierarchies indicate that protective clothing and shade are better options.